Impact of AI on Financial Decision-Making in Team Management – Risk Analysis and Performance Forecasting - Iwona PRZYCHOCKA; Maciej SIKORSKI (Communications of International Proceedings, 2024)
Artificial Intelligence (AI) already has, and is poised to have an even greater, profound impact on financial decision-making and team management. Its influence spans critical areas such as risk analysis, ethical considerations, and performance forecasting. AI enhances decision-making processes by rapidly analyzing vast datasets and uncovering insights that exceed human capabilities. However, this transformative potential brings significant ethical challenges, including algorithmic bias, transparency, and accountability. To ensure AI’s effective and responsible integration, robust ethical frameworks, human oversight, and collaboration with regulatory bodies are crucial. AI is also redefining industries by reshaping labor markets, accelerating automation, and transforming managerial roles. While AI drives efficiency and innovation, concerns around data protection, market stability, and workforce displacement persist. A hybrid approach, blending AI’s technological power with human creativity and empathy, is essential for sustainable and ethical adoption.
Keywords: AI; finance; management; risk; forecast